Tanggung Jawab Negara dalam Memberikan Perlindungan terhadap Hak-hak Korban Pelanggaran HAM Berat di Indonesia - Muhammad Jailani (Syiar Hukum, 2011)
Under the international human rights law, every state has the primary responsibility in the promotion and protection of human rights, that can not be reduced for political, economic and cultural reasons. Indonesia has enacted Law No 39 of 1999 on Human Rights and Law No. 26 of 2000 on Human Rights Court  consistent with the relevant  international human rights instruments. Under Article 71of Law No 39 of 1999 The Indonesian Government is obliged and responsible to respect, protect, enforce, and promote human rights as stipulated in this Law, other legislation, and the human rights international laws ratified by the Republic of Indonesia . In recent years, however, the gross violations of human rights have occurred in Indonesia, which have not yet been settled. The human rights are clearly violated by the Indonesia Authorities both civilian and military officials. This article is to study the legal  redress for the victims of human rights gross violations under the above national laws and Government Regulation No. 3 of 2002. The article will seek to demonstrate gaps in the current legal framework  governing human rights. The continuation of the impunity and injustice treatement  for the human rights victims is a direct result of the inadequate legislation.